IFRS i Norge - Thelin Eltarvåg, Sindre; Aellig Strandvold, Alvar; Thu, Karoline; Bernhoft, Anne-Cathrine; Madsen, Robert; Ragnar Vigdel, Lars; Mørch Hunskaar, Lars; Kleveland, Erik; Rognli, Cato; Møller, Bjarne (Fagbokforlaget Vigmostad & Bjørke, 2026)
Solid knowledge of the content and application of the international accounting standards IFRS (International Financial Reporting Standards) is crucial for those who prepare and read financial statements for listed companies and other companies reporting under IFRS. The ninth edition of the article collection IFRS in Norway – A Handbook is primarily a collection of professional articles illustrating the application of IFRS in practice, and it will be a good supplement to international IFRS literature for those who work with IFRS on a daily basis. The professional approach to the topics, combined with stylized and practical examples, also makes it well suited as a textbook in financial accounting courses in the master’s program in auditing and accounting. This ninth edition has been expanded with four new articles on earnings per share, related parties, the reporting entity and separate financial statements, and first-time adoption of IFRS. The other articles have been updated with new relevant areas and adjustments due to new or amended standards or developments in practice. This year’s edition is also updated with a range of new practice and theory examples, and the collection now contains more than 400 examples.